Peran Tahqῑq al-Manᾱth Dalam Bahtsul Masail PBNU Tentang Vaksin AstraZeneca - Moh Sholeh; Fairuzzaj Muhammad; Rahwan (Wasathiyyah, 2023)
This paper will explain the realization of Tahqi>q al-Mana>t as a science and scientific approach in LBM PBNU regarding the halalness of AstraZeneca vaccine products. Bahtsul Masail’s decision regarding vaccine products from South Korea is holy and halal, considered progress. Because before that, there was already a fatwa on the prohibition of the vaccine. This is inseparable from the process of understanding the nature of vaccines so that they can apply halal (permissible) law to the AstraZeneca vaccine. In this study, we used a type of library research with a fiqh-usul fiqh approach, most of the techniques adopted from a qualitative-descriptive method. Namely describing data from primary and secondary sources then analyzing and describing the results of the research. From this discussion we conclude that Tahqi>q al-Mana>t has a signi-ficant role in the bahtsul masail held by LBM PBNU regarding the halalness of the AstraZeneca vaccine, especially at the stage of understanding the essen-ce (tasawwur) of the AstraZeneca vaccine by referring to the opinions of the experts. Dalam tulisan ini akan dijelaskan realisasi Tahqi>q al-Mana>t sebagai pendekat-an ilmu dan sains dalam LBM PBNU terkait kehalalan produk vaksin Astra-Zeneca. Keputusan bahtsul masail yang menghalalkan produk vaksin asal Korea Selatan, terbilang progres. Karena sebelum itu, sudah ada fatwa keha-raman vaksin tersebut. Hal ini tidak terlepas dari proses dalam memahami hakikat vaksin sehingga bisa menerapkan hukum halal (boleh) terhadap vaksin AstraZeneca. Dalam penelitian ini, kami menggunakan jenis penelitian kepus-takaan (library research) dengan pendekatan fikih usul-fikih yang sebagian be-sar tekniknya mengadopsi dari metode kualitatif-deskriptif, yaitu mendeskrip-sikan data dari sumber primer dan sekunder kemudian melakukan analisa dan mendeskripsikan hasil penelitian. Dari pembahasan tersebut kami menyimpul-kan bahwa Tahqi>q al-Mana>t memiliki peran yang signifikan dalam bahtsul masail yang diselenggarakan LBM PBNU tentang kehalalan vaksin AstraZe-neca, terutama pada tahap pemahaman esensi (tasawwur) vaksin AstraZeneca dengan mengacu pada pendapat para pakarnya.